Surgery for Cancers of the Gastrointestinal Tract A Step-by-Step Approach - Kim, Joseph; Garcia-Aguilar, Julio (Springer New York : Imprint: Springer, 2015)
This book provides an educational resource of modern and advanced operative techniques for patients with GI cancers. The textbook is designed to provide a step-by-step surgical approach, highlighting key learning points and potential operative pitfalls. When appropriate, two or more different approaches on an operative procedure are presented to provide additional perspective on surgical techniques. Written descriptions of laparoscopic and robotic cancer operations are paired with online video presentations of the same cancer operation. Written by experts in the field, Surgery for Cancers of the Gastrointestinal Tract: A Step-by-Step Approach provides a concise summary of the current management of each GI cancer and is of great utility to not only surgeons at all levels of training, but also for surgeons in practice who seek to reinforce or learn new surgical techniques.